PENGARUH CELEBRITY ENDORSER, BRAND IMAGE DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PEMBERSIH WAJAH MEN’S BIORE - Kumala Sukma, Kadek Ayu Dwi Sudias; Nurcahya, I Ketut; Suryani, Alit (E-Jurnal Manajemen, 2016)
The development of information technology which is increasingly sophisticated drives the customers to be able to absorb the information regarding a product or service more easily. Consumers are more selective in choosing the product to be used or consumed nowadays so that consumers will provide a positive response toward a product. The aim of this study is to find out how a celebrity endorser, brand image and trustworthiness affecting toward the decision to purchase the product of Men’s Biore facial cleanser. The research was conducted in Denpasar with data analysis technique of multiple linear regression by using the program of Statistical Package of Social Science (SPSS) version 17.0 for Windows. The determination of sample number was through non probability sampling technique particularly purposive sampling, of 135 respondents. The result of analysis proved that celebrity endorser, brand image and trustworthiness partially affected positively and significantly toward the decision to purchase the product of Men’s Biore facial cleanser in Denpasar city.
Keywords: celebrity endorser, brand image, trustworthiness and purchasing decision